Historia y profecía en el donatismo tardío: el Liber Genealogus - Beltrán Torreira, Federico-Mario (Antigüedad y Cristianismo, 1990)
Although the Christian historgraphy, after the deep revisión carried out by Eusebius of Cesárea, abandoned its original characteristics of confrontation with the Roman Empire and millenary hopes, the same did not occur with Donatism which remained tied to the historical vision of the epoch of the persecutions. This conservative attitude is evident in the LIBER GENEALOGUS, the Latin version of the CHRONICA by Hipolitus of Rome. There are three known editions of this CHRONICA, published in 405/411, 427 and in 438, under the Donatist influence in Carthage. For this reason the publication of 438 is particularly interesting because it not only compares, as the previous ones, the persecutions carried out by the pagan emperors with the measures taken by Honorius against the schismatics, but also goes so far as to consider the incarnations of the Anti-Christ in the Vandal king Genseric and in the Praetorian Perfect, Antemius. A last version, this one Catholic, redacted in 455/63, and notable for its Biblical knowledge, abandons these asumptions, deploring the assassination of Valentinianus III as a catastrophe which marks the inminent end of the world. The progresive integration of the last Donatist circles in the bosom of the Catholic Church had in this way permitted the recuperation of a labor which, now void of its explicit political content, maintained however untouched its strong escatological content.